Penggunaan peralatan dan bahan audio-visual dalam pengajaran di kelas: Tinjauan keefektifan - Rahman, Aini Citra; Hamka, Defrizal (Karoteh Utama, 2020)
This research aims to assess the availability of audiovisual equipment and materials in schools and their practical usage in classroom teaching. The research design used is quantitative descriptive, and the instrument utilized for this research is a questionnaire. The data analysis technique employed is the Miles and Huberman Interactive analysis model. This study was conducted in 5 middle schools, with seven teachers as research subjects. The findings of this research indicate that the status of audiovisual equipment needs to be improved. Computers, televisions, tape recorders, and public address systems are only owned by 64.62% of the schools. Variables such as school management type, school age, school resources, and school strength do not significantly influence the possession of adequate or inadequate equipment in the schools. A total of 87.4% of the schools have effectively used audiovisual equipment. The school administration has yet to make any efforts to properly procure and utilize audiovisual equipment and materials, primarily due to the financial challenges associated with equipment maintenance.